Peran Pendidikan Islami dalam Membentuk Kecerdasan Spiritual Anak Tunadaksa: Studi di SLB IT Sahabat Al-Qur’an Binjai - Ira Rayani; Annisa Fitri; Dewi Marina; Munziah Munziah; Ampun Bantali (Alifbata : Jurnal Pendidikan Dasar, 2025)
This study was conducted to examine the role of Islamic education in shaping the spiritual intelligence of children with disabilities at SLB IT Sahabat Al-Qur'an Binjai. Qualitative methods with a case study approach have been used in this study. Data have been collected through direct observation, in-depth interviews, and documentation. Various religious activities such as congregational prayer, memorizing prayers, learning the stories of the prophets, and practicing morals in everyday life have been consistently implemented and have been proven to contribute to strengthening the spiritual aspects of children. Learning to memorize the Qur'an has also been used as a means of developing self-confidence and emotional stability of children with disabilities. Support from teachers, parents, and the social environment has been identified as a major factor in the success of this process. Thus, an inclusive and adaptive Islamic education approach is highly recommended to be further developed in order to shape the spiritual quotient of children with special needs.